2005
DOI: 10.1038/sj.jea.7500339
|View full text |Cite
|
Sign up to set email alerts
|

Levels of dioxins and furans in plasma of nonoccupationally exposed subjects living near a hazardous waste incinerator

Abstract: The potential adverse effects of hazardous waste incinerators (HWI) continue to be a subject of worry. The construction of the first and till now only HWI in Spain finished in 1999. To assess the potential impact of the plant on public health, a preoperational monitoring program was established during the period of construction. The main goal of the present study was to determine, after approximately 3 years of regular operations in the facility, the concentrations of polychlorinated dibenzo-p-dioxins and dibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The ambient exposure from MWIs could not explain the PCDD/Fs levels in serum, regardless of the fact that PCDD/Fs congener profiles may be alike . Other studies have reported a similar relationship, such that ambient exposure contributes little in serum PCDD/Fs levels (Michalek et al, 1992;Agramunt et al, 2005;Hu et al, 2005;Moon et al, 2005). In a 4-yr follow-up study assessing PCDD/Fs impact in the vicinity of a new hazard waste incinerator, Ferre-Huguet et al (2006) found that the human exposure was mainly due to dietary food intake.…”
Section: Resultsmentioning
confidence: 70%
“…The ambient exposure from MWIs could not explain the PCDD/Fs levels in serum, regardless of the fact that PCDD/Fs congener profiles may be alike . Other studies have reported a similar relationship, such that ambient exposure contributes little in serum PCDD/Fs levels (Michalek et al, 1992;Agramunt et al, 2005;Hu et al, 2005;Moon et al, 2005). In a 4-yr follow-up study assessing PCDD/Fs impact in the vicinity of a new hazard waste incinerator, Ferre-Huguet et al (2006) found that the human exposure was mainly due to dietary food intake.…”
Section: Resultsmentioning
confidence: 70%
“…In 2002, we performed another survey focused on determining the levels of PCDD/Fs in plasma on non-occupationally exposed individuals living in the area under potential inXuence of PCCD/F emissions from the facility. The mean PCDD/F levels were 15.7 pg I-TEQ/ g lipid (Agramunt et al 2005). It is important to note that during the period 1998-2007, the dietary intake of PCDD/ Fs by the population of the County where the HWI is placed was notably reduced from 210 pg I-TEQ/day in 1998 (Domingo et al 1999) to the current 27.8 pg WHO-TEQ/day (Martí-Cid et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…A continued and significant decrease in the plasma levels of PCDD/Fs have been noticed in subsequent surveys included in the surveillance program. Thus, in 2002 (36), 2007 (37) and 2012 (38), the mean PCDD/F concentrations in plasma of subjects living in the neighborhood of the HWI were 15.7, 9.4, and 6.18 pg I-TEQ/g lipid, respectively. In turn, the results of the last study conducted in 2018 (39) showed a mean level of 6.79 pg I-TEQ/g lipid, which was very similar to that found in 2012 (6.18 pg I-TEQ/g lipid) (38).…”
Section: Spainmentioning
confidence: 95%